Relationship between IL1B gene polymorphism and smoking with the risk of myocardial infarction - M. V. Khutornaya; A. V. Ponasenko; Y. V. Bayrakova; A. S. Golovkin (Acta Biomedica Scientifica, 2014)
Genotype and smoking determined risks of myocardial infarction in patients with ischemic heart disease. Homozygous genotype C (rs16944) of IL1B is associated with myocardial infarction (OR = 3,17 (95% Cl = 0,92-10,89); р < 0,01) and heterozygous carrier state of this allelic gene doesn't increase risks (OR = 1,36 (95% CI = 0,83-2,2); р = 0,01). Smoking 5 times increases risk of myocardial infarction (OR = 5,16 (95% CI = 1,05-25,39); p < 0,05) in homozygotes, and 1,5 times (OR = 1,46 (95% CI = 0,77-2,78); p < 0,05) - in heterozygotes of 511Т/С lL1B. Haplotype СТ (rs1143634 - rs16944) of IL1B is connected with the decrease of risk of myocardial infarction in nonsmoking patients (OR = 0,43 (95% DI = 0,19-0,95); р < 0,01).